Domestic violence and work: setting a workplace agenda. (2nd October 2022) - Gavin, Mihajla; Weatherall, Ruth
ABSTRACT: The role and responsibilities of workplaces in responding to domestic violence is emergent. Once considered a 'private' issue which was contained to the home, domestic violence is now recognised as a gendered, social issue that impacts all aspects of a victim's life, including their working life. Although strides have been made in the last two decades to establish economic and ethical mandates for workplace responsibility, there is still a long way to go. This article traces the conceptual and empirical journey of the issue of domestic violence and work in the context of industrial relations as well as management and organisation studies. This journey leads us to the articles contained in the special issue. These articles are at the forefront of practice, policy, and theory of domestic violence and work, and offer a range of vivid insights into the vital work being done in this space. Ultimately, this article sets out a workplace agenda which prioritises continuing dynamic dialogue between theory and practice.